PENGEMBANGAN MULTIMEDIA INTERAKTIF DENGAN MODEL PBL BERBASIS HOTS PADA MATERI MENAFSIRKAN DATA KELAS V SD - M Rizki Dirmansyah; Nur Fitriyana; Andri Valen (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research aims to develop Interactive Multimedia with ModelsPBL BasedI.EIn Material for Interpreting Class V Elementary School Data that is valid, practical and effective. This type of research isRD by using modelsADDIE. The research subjects were fifth grade students at SDN 38 Lubuklinggau. Data collection in research was carried out by observation, interviews, questionnaires and tests. The instruments used are questionnaire sheets, written questions. The research results show that the product developed is valid with an average validity of 0.88 and is practical based on the recapitulation results of teachers' practicality assessments,one to one and small groups with a high classification of 0.88, and are effective in improving student learning outcomes based on scoresN-Gain in large group trials it was 0.73 in the high category. Based on the research results, it was concluded that the product developed was proven to be valid, practical and effective so that it was suitable for use in interpreting class V bar and line diagram data at SDN 38 Lubuklinggau.